Theology of work: new perspectives - Guitián Crespo, Gregorio (New critical thinking in religion, theology and biblical studies, 2025)
"Theology of Work: New Perspectives emerges from the necessity to continue theological reflection on work in light of the challenges posed by our contemporary world. The contributions offer a global perspective of the meaning of work, drawing from Trinitarian theology, theology of creation, eschatology, theological anthropology, and Christology. They shed light from the perspective of faith on the integration of different work dimensions, and consider how the theology of work is called to challenge social structures in the light of revelation. The volume mostly develops the theology of work from a Catholic perspective, but Protestant and Orthodox approaches are also explicitly explored. The chapters cover different theological areas such as biblical, dogmatic, patristic, and moral theology to provide enriching and complementary perspectives. Offering fresh and valuable theological insights on work, this book will be of particular interest to scholars of theology and religious studies"--